Engineering of Self‐Propelling Microbots and Microdevices Powered by Magnetic and Electric Fields. (18th December 2017) - Han, Koohee; Shields, C. Wyatt; Velev, Orlin D.
Abstract: In the last two decades, advances in micro‐ and nanofabrication have enabled the development of a wide variety of active or "self‐propelling" microparticles, which convert energy from their environment into directed motion. While these autonomous entities have shown promise for efficient locomotion on the microscale, their practical utility remains unrealized due to their inability to perform multiple useful tasks on demand. From an engineering perspective, the active particle behavior can be encoded on an individual level by tailoring key design elements such as shape, polarizability, surface pattern, and bulk functionality. This feature article focusses on active particles powered by electric and magnetic fields, as these sources of energy allow the particles to: (1) move in several phenomenologically unique ways, (2) respond in a reliable manner to the field parameters, and (3) interact synergistically to enable multiple functions. It is hypothesized how future generations of such particles may remotely harvest and transduce energy to perform several useful tasks such as biosensing and delivering drugs. As a step toward realizing such particles, several new types of active particles are demonstrated. Finally, a perspective on the future directions of this emerging field is provided by discussing current challenges, potential applications as well as future opportunities. Abstract : Engineered active particles exist outside of equilibrium by harvesting energy to self‐propel. Such particles can in the future perform complex operations such as delivering drugs to remote areas in the body. The use of electric and magnetic fields allows these particles to move in complex trajectories by independently propelling and steering them, and powering additional functionalities.